Cardiovascular disease burden in the homeless population - Jeffrey R Harris; Samhita Korukonda; Nikith Erukulla; Pranitha Kovuri; Kenneth Tyler Wilcox (Open Heart)
Introduction The burden of cardiovascular disease (CVD) among the homeless population has been rising, driven by factors such as lack of healthcare access, rising mental health disorders and substance use. This study aims to systematically analyse the CVD burden among homeless adults and characterise its prevalence and risk factors. Additionally, our literature review revealed a significant lack of cardiac-focused interventions in this population, thus we build on existing models to propose new CVD-specific interventions.Methods A comprehensive systematic review and meta-analysis were performed on data collected from PubMed and Scopus until 22 October 2024. All observational studies that assessed homeless populations and met inclusion criteria were analysed. The primary outcomes reported were mortality, morbidity and hospitalisation due to CVD. These measures were collectively analysed to evaluate the overall CVD burden.Results Our search strategy identified 22 studies, of which 12 were suitable for meta-analysis. We analysed data from 226 205 adults spanning more than 1 000 000 person-years and sought to characterise CVD distribution by demographic subgroups. Our findings indicate that homeless adults experience greater morbidity and mortality due to CVD than non-homeless adults (pooled OR 2.77; 95% CI 1.93 to 3.93; p<0.001; I2=96.2%). Subgroup analyses by age, sex and geographic region were performed, but no significant differences in CVD morbidity and mortality were found.Conclusion Homeless adults have approximately three times greater odds of CVD than the general population. We found that the risk of CVD remains elevated regardless of demographic subgroup. Our findings emphasise the urgent need for targeted interventions within this population and highlight its associated risk factors, providing a foundation for the development of targeted interventions and policies.